2018
DOI: 10.29016/180419.1
|View full text |Cite
|
Sign up to set email alerts
|

Origins to Outcomes: A Role for Extracellular Vesicles in Precision Medicine

Abstract: Extracellular vesicles (EVs) are of great interest in biological research, and though they are a relatively recent discovery, they have rapidly shown great potential for use in clinical applications. The various techniques used in EV isolation along with their respective strengths, weaknesses, and potential for downstream applications are outlined here. A brief description of the different approaches in exosome characterisation are subsequently described. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
(179 reference statements)
0
3
0
Order By: Relevance
“…Additionally, the lack of highly repeatable standard protocols for the measurements of all critical sample attributes, combined with the lack of reference materials are also impacting the reproducibility of EV characterization within acceptable industrial confidence variance. Such lack of fundamental knowledge is probably slowing down both the basic research and the regulatory approval process in this area, as reported by some of the authors previous works (Gioria et al, 2018;Hole et al, 2013;Savage et al, 2018). While attempting to provide clear answers to the EV community in term of reproducibility, accuracy and acceptability, this work is focussed on an in-depth analysis of the key EV isolate quality attributes: concentration and size distribution.…”
Section: Nta Trps Nfcm Cls Af-mals Madlsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the lack of highly repeatable standard protocols for the measurements of all critical sample attributes, combined with the lack of reference materials are also impacting the reproducibility of EV characterization within acceptable industrial confidence variance. Such lack of fundamental knowledge is probably slowing down both the basic research and the regulatory approval process in this area, as reported by some of the authors previous works (Gioria et al, 2018;Hole et al, 2013;Savage et al, 2018). While attempting to provide clear answers to the EV community in term of reproducibility, accuracy and acceptability, this work is focussed on an in-depth analysis of the key EV isolate quality attributes: concentration and size distribution.…”
Section: Nta Trps Nfcm Cls Af-mals Madlsmentioning
confidence: 99%
“…EVs can be subclassified into several different subsets based on biogenesis (Akers et al., 2013; Théry et al., 2018), in order of increasing size, such as exosomes (< 150 nm), microvesicles (> 100 nm) and apoptotic bodies (> 100 nm) (Hessvik & Llorente, 2018). EVs have been considered a recent avenue for biomedical investigation in both regenerative and pathogenic contexts, with potential in diagnostic and therapeutic applications (Savage et al., 2018). Their potential use in manifold applications, including drug delivery, particle loading and other theragnostic applications have been reviewed recently (Piffoux et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation